Internet literacy - Hofstetter, Fred T. (Boston : Irwin/McGraw-Hill, 1998)
Understanding the Internet. Getting on the Internet. Communicating over the Internet. Finding things on the Internet. Creating Web pages...
Keywords: Internet literacy; Internet literacy